DRYAD - Data Sharing Best Practices for Researchers and Institutions Working with AfricArXiv - Guerreiro, Maria; Lippincott, Sarah; Masisi, Keletso (My University, 2024)
This session is part of the AfricArXiv Webinar Series on Open Science for the Discoverability of African Research.
Watch the recording https://africarxiv.pubpub.org/pub/v87bgk80#n15xl15cdhb
Keywords: AfricArXiv; DRYAD; Data sharing